Comparative Effects of Neem (Azadirachta Indica) Extracts and Karate (Lambdacyhalothrin) in the Control of the Root Knot Nematode (Meloidogyne Incognita) on Celosia Argentea (2013)
In order to compare the effects of lambdacyhalothrin, a synthetic pyrethriods and neem (Azadirachta indica) extracts in the control of the root knot nematode of Celosia argentea, two weeks old plants of C.argentea were inoculated with 7,000 eggs of Meloidogyne incognita. Seven days after inoculation, the plants were treated with two concentrations of lambdacyhalothrin at 6,000ppm and 3,000ppm and neem oil extract at 2.14 ml/kg and 4.28ml/kg of soil. Untreated nematode-inoculated C.argentea plants served as negative control while uninoculated C. argentea plants served as positive control. Three weeks after inoculated and subsequently till the 8th week, data were collected on growth parameters such as stem height, number of leaves and yield parameters such as fresh shoot weight, fresh root weight, and root galling indices. There were significant differences between the untreated-nematode inoculated plants, had the lowest values. There were also no significant differences between Lambdacyhalothrin-treated plants at both 6000ppm and 3000ppm for all the parameters considered. Thus, neem oil at 2.14 ml/kg of soil is recommended as an alternative for Lambdacyhalothrin at 6000ppm and 3000ppm concentrations in the control of root knot nematode of C.argentea since the leaf is the most important part and in view of its environment friendliness